2007
DOI: 10.1002/hbm.20385
|View full text |Cite
|
Sign up to set email alerts
|

Neuromagnetic functional coupling during dichotic listening of speech sounds

Abstract: The present magnetoencephalography (MEG) study tested the hypothesis of a phase synchronization (functional coupling) of cortical alpha rhythms (about 6-12 Hz) within a "speech" cortical neural network comprising bilateral primary auditory cortex and Wernicke's areas, during dichotic listening (DL) of consonant-vowel (CV) syllables. Dichotic stimulation was done with the CV-syllable pairs /da/-/ba/ (true DL, yielded by stimuli having high spectral overlap) and /da/-/ka/ (sham DL, obtained with stimuli having p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 74 publications
2
24
0
1
Order By: Relevance
“…The different spatial distribution of the effects, and in particular the left hemispheric bias for the vowel but not the speaker task, indicates the involvement of distinct networks of brain areas. Based on this observation and the putative role of alpha oscillations in modulating functional connectivity between brain areas (von Stein et al, 2000;Kujala et al, 2007;Brancucci et al, 2008), we hypothesize that the observed phase reorganization operates at an interregional level. In particular, this reorganization may mediate temporal binding of distributed neural activity in distinct (auditory) cortical areas subserving the abstract representation of voice and speech (Formisano et al, 2008).…”
Section: Cortical Coding Of Vowel/speaker Invariancementioning
confidence: 74%
“…The different spatial distribution of the effects, and in particular the left hemispheric bias for the vowel but not the speaker task, indicates the involvement of distinct networks of brain areas. Based on this observation and the putative role of alpha oscillations in modulating functional connectivity between brain areas (von Stein et al, 2000;Kujala et al, 2007;Brancucci et al, 2008), we hypothesize that the observed phase reorganization operates at an interregional level. In particular, this reorganization may mediate temporal binding of distributed neural activity in distinct (auditory) cortical areas subserving the abstract representation of voice and speech (Formisano et al, 2008).…”
Section: Cortical Coding Of Vowel/speaker Invariancementioning
confidence: 74%
“…However, the tendency for perceptual fusion strongly depends on the phonological properties of the contrasted stimuli even when they appear very similar (Repp, 1976). For example, when using plosives as initial phonemes, the voicing of the stimuli systematically affects the spectro-temporal overlap of the two auditory channels (Brancucci et al, 2008). Voiced syllables, such as /ba/ or /da/, are characterized by strong rhythmic vibrations of the vocal cord during articulation, while unvoiced syllables, such as /pa/ or /ta/, do not show such vibrations.…”
Section: Inter-channel Onset and Offset Alignmentmentioning
confidence: 99%
“…Mediante magnetoencefalografía, empleando escucha dicótica de sílabas con voice onset time breve o largo, agrupadas en pares breve-largo, largo-largo, breve-largo y largo-breve para cada oído, parece que el acoplamiento de las diferentes bandas de ritmo alfa constituye el sustrato neurofisiológico de la lateralización de los estímulos verbales en tarea dicótica, al menos en lo que se refiere a la corteza auditiva y a la corteza asociativa implicada en el reconocimiento del material lingüístico [43]. En la actualidad, la resonancia magnética funcional durante la realización de tareas verbales es la referencia más precisa para estudiar la organización jerárquica interhemisférica e intrahemisférica del lenguaje en preescolares [44], e incluso en lactantes pequeños [45], y ha desplazado al test del amital sódico en estudios de jerarquización topográfica (no sólo interhemisférica, sino también intrahemisférica) de las funciones cerebrales superiores en adultos y en niños.…”
Section: Discussionunclassified